Essentials of accounting for governmental and not-for-profit organizations - Copley, Paul A. (McGraw-Hill/Irwin, 2011)
Copley's Essentials of Accounting for Governmental and Not-for-Profit Organizations, 10/e is best suited for those professors whose objective is to provide more concise coverage than what is available in larger texts. There is more comprehensive coverage of accounting for governmental and not-for-profit organizations than what is available in an advanced text but concise enough to be used effectively in a semester, quarter, or even a half term course focusing on just these areas